VANILLA YERSINIANA (ORCHIDACEAE), A NEW RECORD FOR PENINSULAR MALAYSIA - Muhammad Ikhwanuddin, Mat Esa; Farah Alia, Nordin; Rusea, Go; Mohd Akmal, Mohd Raffi (Herbarium Bogoriense, Botany Division, Research Center for Biology-LIPI, Cibinong Science Center, 2021)
ESA, M. I. M., NORDIN, F. A., GO, R. & RAFFI, A. 2021. Vanilla yersiniana (Orchidaceae), a new record for Peninsular Malaysia. Reinwardtia 20(2): 49 − 53. — The genus Vanilla Plum. ex Mill. from Peninsular Malaysia is now enriched with the discovery of a newly recorded species, Vanilla yersiniana that made up its regional diversity to eight taxa. This species was documented from two adjacent secondary lowland forests in Perak; further south to the southern tail of Thailand. This paper describes the first record of V. yersiniana in Peninsular Malaysia with some high-lights of its morphology and ecology. The data presented will add to the present state of knowledge on the species botanical profile.